CLINICAL AND LABORATORY PARAMETERS OF THE WOUND PROCESS COMPLICATED BY THE SYSTEMIC INFLAMMATORY RESPONSE SYNDROME IN PATIENTS WITH DIABETES MELLITUS - Khamdamov, B.Z.; Dekhkonov, A.T. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
The relentless increase in the incidence of surgical soft tissue infections requires more and more attention from medical societies to pay attention to this problem. Special cases are considered when a surgical soft tissue infection is complicated by a systemic inflammatory response syndrome. As you know, such cases are a priority among patients with diabetes mellitus. In this article, we present the results of our own analytical studies on the assessment of the clinical picture and clinical and laboratory signs of the course of purulent-inflammatory diseases of soft tissues complicated by the systemic inflammatory response syndrome in patients with diabetes mellitus. We found that the frequency of occurrence of certain clinical and laboratory signs of the systemic inflammatory response syndrome was ambiguous. The dynamics of changes has a certain regularity. At the same time, the analysis of the microbiological picture of a wound infection complicated by a systemic inflammatory response syndrome in patients with diabetes mellitus showed a staging of changes in both the quantitative and qualitative nature of pathogens in the dynamics of the treatment.